Which Matters More for Medication Adherence Among Disabled People in Shanghai, China: Family Support or Primary Health Care?. (October 2019) - Huang, Jiaoling; Jiang, Zhiyun; Zhang, Tao; Wang, Luan; Chu, Yiming; Shen, Mei; Liang, Hong; Liu, Shanshan; Zhang, Yimin; Liu, Chengjun
Most disabled people have poor health status. They often have multiple diseases requiring continual medication. This study aimed to explore the factors associated with medication adherence among disabled people, with a particular focus on the factors associated with family and primary health care support. A questionnaire survey was conducted among 226 disabled individuals. The analysis was performed using an ordered logistic regression model, including 4 categories of predictor variables. We found that the community health service center played a positive role in improving medication adherence, whereas the role played by the participant's family was more complicated. Specifically, those obtaining a brochure were more likely to have higher medication adherence (odds ratio [OR] = 2.732, 95% confidence interval [CI] = 1.349-5.532). Compared with those who were married, widowed participants (OR = 0.207, 95% CI = 0.069-0.620) and divorced participants (OR = 0.330, 95% CI = 0.057-1.914) had lower odds of having greater adherence, whereas the odds of having greater adherence for single participants were 1.679 times the same odds for married participants (OR = 1.679, 95% CI = 0.668-4.224). The odds of having greater medication adherence for participants receiving help with prescriptions from a family member were almost 60% lower than these odds for those who did not receive this kind of help (OR = 0.460, 95% CI = 0.216-0.979). Thus, the role played by participants' family members was both protective and damaging, whereas the role of the community health service center was clearer. These findings merit further exploration.